2015
DOI: 10.1016/j.eats.2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Rotator Cuff Tear Transosseous Repair System: The Sharc-FT Using the Taylor Stitcher

Abstract: Transosseous rotator cuff tear repair was first described in 1944. Over the years, it has represented the gold standard for such lesions. Through open and mini-open approaches, as well as the arthroscopic approach, the transosseous repair system represents one of the most reliable surgical techniques from a biological and mechanical perspective. Nevertheless, further improvements are required. This article describes an arthroscopic rotator cuff tear transosseous repair system, developed in collaboration with N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…The authors concluded that the patient satisfaction rate was high, no patients expressed concern about the implant, and the complication rate was very low. 13 In the present study, despite the relatively short follow-up time, our outcomes are concordant with previous reports, and no bone cutting phenomena, impingement with the acromion, or implant failure was noted with this new device. The mean clinical and functional outcomes 16.8 months after surgery showed significant improvements in the Q-DASH and Constant-Murley scores compared to the preoperative status ( p < 0.05).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The authors concluded that the patient satisfaction rate was high, no patients expressed concern about the implant, and the complication rate was very low. 13 In the present study, despite the relatively short follow-up time, our outcomes are concordant with previous reports, and no bone cutting phenomena, impingement with the acromion, or implant failure was noted with this new device. The mean clinical and functional outcomes 16.8 months after surgery showed significant improvements in the Q-DASH and Constant-Murley scores compared to the preoperative status ( p < 0.05).…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, we used a novel transosseous device supplied with three additional and complementary tools: an inserter, a punch, and a multipurpose tool for fitting/removing the super elastic transosseous needle. 8,13 The punch instead allows a hole to be made where placing the transosseous device. In addition, the super elastic transosseous needle allows for the creation of one or more transosseous tunnels in the lateral entry hole in which the device is entered and one or more medial exit holes adjacent to the footprint field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, transosseous rotator cuff repair, first described in 1944 by McLaughlin, is considered the gold standard for rotator cuff surgery by many authors. 13,21 Over the past few years, many authors have described slightly differing versions of arthroscopic transosseous rotator cuff repair (ATORCR). 2,7,8,13,14,16,21 This method theoretically represents the best of both worlds, having the advantage of a minimally invasive arthroscopic procedure with the strength and cost-effectiveness of transosseous fixation.…”
mentioning
confidence: 99%